Osteochondrosis of the primary ossification center of the patella (Kohler's disease of the patella) report of three cases - Pinar, H; Gül, O; Boya, H; Özcan, C; Özcan, Ö (Springer-Verlag, 2002)
Radiography of three boys 5-6 years old with anterior knee pain revealed increased density and irregularity of the patellar ossification centers. A search of the literature suggested that it was osteochondrosis of the primary ossification center of the patella, named after Kohler. Continuing search also revealed that it might be a normal variant instead of an osteochondrosis. A short course of activity modification led to marked improvement in all. The patients were either asymptomatic or experienced minor symptoms 18-34 months after presentation. It was concluded that the process, either physiological or pathological, has a benign course and favorable prognosis.
Keywords: osteochondrosis; patella